1998
DOI: 10.1038/4013
|View full text |Cite|
|
Sign up to set email alerts
|

Hyperglycemia induces apoptosis in pre-implantation embryos through cell death effector pathways

Abstract: Although perinatal mortality rates have improved for pregnant diabetic women because of insulin therapy and tight metabolic control, infants of diabetics still experience significantly higher rates of congenital malformations and spontaneous miscarriages compared with those of non-diabetic women. Our results here indicate that hyperglycemic conditions, either in vivo or in vitro, modulate the expression of an apoptosis regulatory gene as early as the pre-implantation blastocyst stage in the mouse. Apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
214
2
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(234 citation statements)
references
References 25 publications
10
214
2
7
Order By: Relevance
“…They proposed that, if this threshold was crossed, an apoptotic pathway was triggered leading to loss of key cells required for optimal survival (88,89). These findings all point to GLUT3 being a critical transporter protein required for this stage of development.…”
Section: Glut3 In the Embryomentioning
confidence: 86%
See 1 more Smart Citation
“…They proposed that, if this threshold was crossed, an apoptotic pathway was triggered leading to loss of key cells required for optimal survival (88,89). These findings all point to GLUT3 being a critical transporter protein required for this stage of development.…”
Section: Glut3 In the Embryomentioning
confidence: 86%
“…These findings were consistent with those of Pantaleon et al (99), in which downregulation with antisense oligoneucletides induced a similar decrease in glucose uptake. In addition, Moley et al demonstrated increased apoptosis and an abnormal metabolic profile (25,88). In vitro culture in high glucose concentrations induced the same decrease in GLUT3 expression and when transferred into recipient mice, these embryos displayed intrauterine growth retardation and a high incidence of fetal resorptions (133).…”
Section: Glut3 In the Embryomentioning
confidence: 99%
“…Hyperglycemic conditions either in-vivo or in-vitro cause downregulation of glucose transporters, decreased glucose transport into cells, abnormal metabolism, and increased apoptosis in cells of preimplantation embryos [91][92][93]. This hyperglycemia-induced apoptosis of progenitor cells in the embryo can affect differentiation of the remaining cells, manifesting later as malformations or miscarriages.…”
Section: Glucosementioning
confidence: 99%
“…Furthermore, enhanced production of ROS is reportedly an important stimulus in the induction of mitochondrial transition, caspase activation and apoptosis [23,24]. Moreover, hyperglycaemia induces apoptosis in early organogenesis in pre-and post-implantation rodent embryos through cell-death effector pathways [25][26][27][28][29]. Also, neural tube defects (NTDs) are associated with apoptosis in the offspring of diabetic mice [30,31].…”
Section: Introductionmentioning
confidence: 99%